2016
DOI: 10.1186/s13071-016-1409-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of Cryptosporidium spp., Enterocytozoon bieneusi and Giardia duodenalis in dogs and cats in Shanghai, China

Abstract: BackgroundControversies exist on the potential role of companion animals in the transmission of enteric pathogens in humans. This study was conducted to examine the genotype distribution of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in companion animals in Shanghai, China, and to assess their zoonotic potential.MethodsFecal specimens from 485 dogs and 160 cats were examined for the occurrence and genotype distribution of the three pathogens by PCR. PCR products were sequenced to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
87
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 38 publications
18
87
3
Order By: Relevance
“…can cause severe generalised encephalitozoonosis or cataracts and uveitis in cats, these zoonotic agents are probably relatively rare, as evidenced by low seroprevalence (2%) in healthy cats (Buyukmihci et al 1977, Hsu et al 2011, Rebel-Bauder et al 2011). Whereas 13 genotypes of E. bieneusi have been reported in cats (Karim et al 2014), we detected only genotype D, which is one of the most frequently reported genotypes (Santín et al 2006, Xu et al 2016. In contrast to previous surveys (Dengjel et al 2001, Xu et al 2016), we did not find E. bieneusi in pet cats.…”
contrasting
confidence: 93%
See 4 more Smart Citations
“…can cause severe generalised encephalitozoonosis or cataracts and uveitis in cats, these zoonotic agents are probably relatively rare, as evidenced by low seroprevalence (2%) in healthy cats (Buyukmihci et al 1977, Hsu et al 2011, Rebel-Bauder et al 2011). Whereas 13 genotypes of E. bieneusi have been reported in cats (Karim et al 2014), we detected only genotype D, which is one of the most frequently reported genotypes (Santín et al 2006, Xu et al 2016. In contrast to previous surveys (Dengjel et al 2001, Xu et al 2016), we did not find E. bieneusi in pet cats.…”
contrasting
confidence: 93%
“…Whereas 13 genotypes of E. bieneusi have been reported in cats (Karim et al 2014), we detected only genotype D, which is one of the most frequently reported genotypes (Santín et al 2006, Xu et al 2016. In contrast to previous surveys (Dengjel et al 2001, Xu et al 2016), we did not find E. bieneusi in pet cats.…”
contrasting
confidence: 93%
See 3 more Smart Citations